PEMBUATAN SISTEM INFORMASI PEMETAAN IBU HAMIL RISIKO TINGGI (STUDI KASUS DI PUSKESMAS BANYUBIRU) - Anggi Ardyansyah; Yudhy Dharmawan; Djoko Nugroho (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Based on initial observation, maps of pregnant mother takes a long time to make while the information included is not maximal. The goal of this research is to make an Information System for mapping high risk pregnant mother. This research uses the “Research and Development” Method. The subject of this research is the midwife who works in Puskesmas Banyubiru Kabupaten Semarang.To make the Information System for mapping high risks pregnant mother, prototyping process model is used. The prototyping process includes the fulfillment of things necessary for the mapping of highrisks pregnant mother, planning the prototype, the making of the prototype, evaluation and improvement. The fulfillment of things necessary for the mapping of high risks pregnant mother is done by interview, observation and the usage of secondary data. The planning and making of the prototype is based on the result of the fulfillmen of things necessary for the mapping of high risk pregnant mother. Evaluation is done by researcher and user using the black box method. Improvement is done based on the result of the evaluation while paying attention to the needs of the user of the system (the midwife). The result of this research is an Information System for mapping high risks pregnant mother. The user is satisfied with the Information System that is made. The Information System is fully functional. The system that made already showing the number of high risk pregnant mother but still needs to be developed in order to apply GPS technology so get high risk pregnant woman distribution and producing a map that more accurate.